Penyuluhan Kesehatan Gigi dan Mulut di SDN 1 Karangkendal Kabupaten Cirebon - Ira Faridasari; Reni Aggraeni (Health Care : Journal of Community Service, 2025)
Oral health is an integral component of general health. It is also clear that the causative and risk factors for oral disease are often the same as those involved in general disease. Data from the Basic Health Research in 2018, Indonesia experienced 57.6% of dental and oral health problems. According to data from the Indonesian Health Survey (SKI, 2023), dental and oral health problems were 56.9%, which means there was a decrease of 0.7% from 2018. The purpose of the dental and oral health counseling activity is to introduce students to dental and oral health and the importance of maintaining dental and oral health. The target of this dental and oral health counseling was grade 2 students of SDN 1 Karangkendal, Kapetakan District, Cirebon Regency. This activity was carried out in class 2A. From the dental and oral health counseling activity, quite significant results were obtained. The results showed an increase in knowledge. Dental and oral health counseling at SDN 1 Karangkendal had a positive impact in increasing students' knowledge about the importance of maintaining dental and oral hygiene and health from an early age. With interactive delivery methods and direct practice, students become more aware of how to properly care for their teeth and mouth. This counseling also helps instill good habits in everyday life to avoid dental and oral diseases.